EXTENT AND LEVEL OF UTILIZATION OF INFORMATION SOURCES AMONG GOAT OWNERS IN INDIA (Indian Journal of Animal Production and Management, 2015)
A study with the objectives to assess the pattern of information utilization was carried out among goat owners in purposively selected states of West Bengal and Uttar Pradesh with a sample size of 180 randomly selected respondents. The study shows the accessibility and extent of utility of different information sources. Total Rank Order Score (TROS) shows that informal interpersonal sources were more used by the goat owners than formal interpersonal and mass media sources. The study reveals that informal interpersonal sources were used for all types of information such as breeding, feeding, healthcare, management and marketing of goat while formal interpersonal sources were used for healthcare, breeding, feeding and management. The study further shows that the goat owners had low level of mass media and formal interpersonal sources utilization while utilization of informal interpersonal sources was medium.
Keywords: Goat owners; Information sources; Mass medi; Total rank order score